STRATEGI PENINGKATAN LITERASI POLITIK PEMILIH PEMULA BERBASIS DIGITAL DI KABUPATEN KUBU RAYA - Syarifah Nurma Afhiani; Grace Melisa Putri; Yesika Yesika (Universitas Hamzanwadi, 2024)
Digital-based political literacy is the ability of individuals to access, evaluate, understand, and use political information presented through digital media critically and effectively.Digital literacy in the Batu Ampar area is quite difficult to develop due to remote terrain, limited internet access and a lack of staff to educate or provide assistance to first-time voters.The aim of this research on digital-based political literacy is to analyze strategies to enhance the understanding and skills of young voters as first-time voters in accessing, evaluating, and using political information, as well as encouraging individuals to participate actively in political processes. The method used in this study is descriptive qualitative, focusing on analyzing strategies to improve political literacy for first-time voters in the use of digital media. The results of the research indicate five strategies to enhance digital-based political literacy for young generations as first-time voters in Kubu Raya Regency: 1) digital literacy corner programs; 2) access to information through credible media; 3) technology volunteers or digital ambassadors; 4) private sector collaboration through wireless information technology; 5) development of digital political literacy materials for young voters.